L’enseignement des pratiques polyphoniques vocales de jazz et de musiques actuelles - Eric Fardet (Recherches en Éducation)
In France, the articulation between the specific model of “conservatoires” (establishments recovering from Ministry of Culture) and art education dispensed by Ministry of National Education remains to specify in particular for teaching of current vocal practice. The actual implementation of decentralization, the reorganization of higher artistic education and the development of amateur practice is an opportunity to examine cultural policies, particularly the effective place of vocal jazz groups in current practice, by promoting synergies between various protagonists, associations, Regions and State.